Components of Integrated Management - Laoluecha, Tiwakorn (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
The components of integrated management used in this article refer to the opinions of the sample on management or the implementation of the integrated administration in the provision of public services, approaches for participating in the partnership between the public and private sectors in the Eastern Special Development Zone project Able to operate and achieve objectives that are in a direction that is conducive to the benefit of the people and the nation. The author of the article has synthesized the variables into 7 variables: Component 1, Organizational (Organizing), Component 2, Policy (Policy) Component 3, Personnel Management (Staff), Component 4, Management Behavior (Style) Component 5, System and Operation Method Component 6 Shared values and Component 7 Skills.